Botho Strauβ: Myth, Community and Nationalism in Germany - Pan, David (Telos, 1995)
Since the end of communism and the reunification of Germany, writers from both the former East and West Germany have sounded the alarm against the materialism of German culture, the dangers of capitalist homogenization, and the decline of values. An entire generation of "leftwing" writers, including Heiner Müller, Botho Strauβ, Hans Magnus Enzensberger, and Martin Walser have attempted to defend German culture against the perceived threat of American capitalism and Western rationalism. Their concerns have led to another call to arms launched by critics, who see in such rhetoric an ominous return to themes already taken up by far Right intellectuals during the Weimar Republic, the Third Reich, and more recently within the German New Right of the 1990s.